Development of an Integrated Electric Vehicle Learning Simulator (EVLIS) with Industry-Based Learning to Accelerate Work Readiness of Vocational School Students - Sudarsono, Bambang; Arief Ghozali, Fanani; Tentama, Fatwa; Asti Mulasari, Surahma; Wahyuni Sukesi, Tri; Sulistyawati, Sulistyawati; Yuliansyah, Herman; Nafiati, Lu'lu'; Listyaningrum, Prabandari; Pratama, Wegig; R. Hafid Hardyanto, Settings; Rahmawati, Rahmawati (Bulletin of Pedagogical Research, 2024)
Technological developments in this modern era require changes in educational approaches to ensure that students have skills that are relevant to the needs of industry, especially electric vehicles. The research aims to develop an industrial integrated electric vehicle learning tool and test its feasibility. This research design adopts Richey and Klein's research and development (R&D) stages with development and internal validation stages. The research objects were carried out at four vocational schools in the Special Region of Yogyakarta and the Automotive Jogjakarta Center (OJC) with research subjects being teachers, experts and industrial practitioners. The resulting research is the competency aspects needed by the electric vehicle industry and the design of electric vehicle learning aids/Electric Vehicle Learning Simulator (EVLIS) that are feasible and ready to be made into product prototypes. EVLIS can help improve the attitude competency, knowledge and skills of electric vehicle technology for vocational school students. Not only that, the development of EVLIS involving the electric vehicle industry can strengthen collaboration/partnership between the industrial world and vocational schools. Keywords: Electric Vehicle Learning Simulator (EVLIS), Industry Based Learning, Work Readiness, Vocational High Schools (SMK)